Adapting an evidence-based mindfulness-based intervention for sheltered youth experiencing homelessness - Diane Santa Maria; Paula Cuccaro; Kimberly Bender; Erica Sibinga; Natalie Guerrero; Najiba Keshwani; Jennifer Jones; Micki Fine (BMC, 2023)
Abstract Objectives Youth experiencing homelessness (YEH) face challenges that impact their physical, mental, and social wellbeing, emotion regulation, and coping. Mindfulness reduces stress and improves resilience, emotion regulation, and executive functioning. Mindfulness-based interventions (MBI) teach the practice of mindfulness to foster present-moment attention without judgement and enhance self-observation and self-regulation, resulting in greater awareness of thoughts and emotions and improved interpersonal relationships. One such intervention, .b, has been shown to lower stress among youth. While a pilot study of .b among sheltered youth found the intervention to be feasible, the need for modifications was identified to improve its relevance, accessibility, and incorporate a trauma-informed approach. Methods We used the ADAPT-ITT (Assessment, Decisions, Administration, Production, Topical experts, Integration, Training staff, and Testing) framework to adapt the .b mindfulness intervention to YEH living in an emergency shelter. Nine focus group discussions (n = 56), key informant interviews (n = 8), and beta testing with five youth working group sessions (n = 10) identified needed modifications. Results Adaptations to the curriculum and delivery modality were made to approximate the average length of stay in the shelter; integrate trauma-informed care approaches; increase diversity of images by race, ethnicity, age, sexual orientation, and gender identity; and increase the relevance of the audio-visual components. Conclusions Youth and the health and social services providers who care for youth generally liked the core concepts and presentation of the curriculum. Using the ADAPT-ITT framework, minor, yet important, changes were made to increase the relevance, acceptability, and feasibility of the intervention. Next steps are to conduct a randomized attention control pilot study to assess feasibility and acceptability.